2013
DOI: 10.1371/journal.pone.0064608
|View full text |Cite
|
Sign up to set email alerts
|

Does Naloxone Reinstate Secondary Hyperalgesia in Humans after Resolution of a Burn Injury? A Placebo-Controlled, Double-Blind, Randomized, Cross-Over Study

Abstract: IntroductionDevelopment of secondary hyperalgesia following a cutaneous injury is a centrally mediated, robust phenomenon. The pathophysiological role of endogenous opioid signalling to the development of hyperalgesia is unclear. Recent animal studies, carried out after the resolution of inflammatory pain, have demonstrated reinstatement of tactile hypersensitivity following administration of μ-opioid-receptor-antagonists. In the present study in humans, we analyzed the effect of naloxone when given after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(61 citation statements)
references
References 60 publications
(66 reference statements)
1
60
0
Order By: Relevance
“…In summary, LS represents a predisposition to relapse that may explain the episodic nature and vulnerability to stress that accompanies chronic pain syndromes in humans (Le Roy et al, 2011, Corder et al, 2013), and thus may reflect a critical mechanism responsible for the transition from acute to chronic pain (Rivat et al, 2007). However, LS has not been reported in humans (Pereira et al, 2013), and our understanding of mechanisms of CNS synaptic plasticity in LS is limited to an involvement of NMDAR. Although the cellular mechanisms underlying LS are now emerging (see below and Corder et al), its synaptic basis remains poorly understood and so this is the focus of intense ongoing investigations.…”
Section: Spinal Mechanisms Of Persistent Painmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, LS represents a predisposition to relapse that may explain the episodic nature and vulnerability to stress that accompanies chronic pain syndromes in humans (Le Roy et al, 2011, Corder et al, 2013), and thus may reflect a critical mechanism responsible for the transition from acute to chronic pain (Rivat et al, 2007). However, LS has not been reported in humans (Pereira et al, 2013), and our understanding of mechanisms of CNS synaptic plasticity in LS is limited to an involvement of NMDAR. Although the cellular mechanisms underlying LS are now emerging (see below and Corder et al), its synaptic basis remains poorly understood and so this is the focus of intense ongoing investigations.…”
Section: Spinal Mechanisms Of Persistent Painmentioning
confidence: 99%
“…We recently reported that low dose naloxone (0.021 mg/kg, i.v. ), delivered following resolution of hyperalgesia after cutaneous heat injury, did not reinstate heat hyperalgesia (Pereira et al, 2013). Rather than limited tissue injury of the model or species differences, this negative result was likely due to insufficient blockade of endogenous opioid receptors, as higher doses of naloxone have been used to demonstrate reinstatement in humans (M.P.…”
Section: Conceptual Model Conclusion and Clinical Significancementioning
confidence: 99%
“…[13] The participants were instructed to use a hair trimmer in the assessment area 2 days before the study, to avoid any interference with the sensory assessments. In case of inadequate trimming, the investigator removed any hair in the assessment area using a surgical hair trimmer (Surgical Clipper 9681, 3M Healthcare, MN).…”
Section: Methodsmentioning
confidence: 99%
“…First , over the course of our previous study to back-translate the human thermal injury model to a rodent model, it was revealed that doses of 3.0 to 10.0 mg/kg of naloxone, delivered 21 days after heat injury to the skin of the plantar hindpaw, were required to precipitate reinstatement of hypersensitivity. [11] Second , in our previous human studies in the heat injury model, low-dose naloxone infusion (21 μg/kg) [13] did not reinstate secondary hyperalgesia, whereas high-dose naloxone infusion (2.0 mg/kg) did precipitate reinstatement in 4 out of 12 subjects. [14] …”
Section: Safety Issuesmentioning
confidence: 99%
See 1 more Smart Citation